2014
DOI: 10.1111/ene.12592
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease incidence and prevalence assessment in France using the national healthcare insurance database

Abstract: The specific and sensitive definitions of disease bracket the true values; the relatively small range indicates that the current study provides good estimations of incidence and prevalence of Parkinson's disease for recent years in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 15 publications
(25 reference statements)
3
43
3
2
Order By: Relevance
“…Our incidence rates are higher than those of Blin, Dureau‐Pournin9 who also used claims data in France and different validation strategies based on ICD codes and drug prescriptions. In contrast to our approach, this French study required a PD diagnosis to be confirmed by two different physicians.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our incidence rates are higher than those of Blin, Dureau‐Pournin9 who also used claims data in France and different validation strategies based on ICD codes and drug prescriptions. In contrast to our approach, this French study required a PD diagnosis to be confirmed by two different physicians.…”
Section: Discussionmentioning
confidence: 70%
“…Generally, PD is rare before age 60 (0.13%‐1.6%), increases with age, and can reach a maximum of 9% among people aged 80‐84. Thereafter (85‐89), prevalences decline and vary from 0.87% to 3.6% 3, 4, 5, 6, 7, 8, 9, 10. Incidence rates are also low for those aged 50‐59 and increase sharply afterward.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, French healthcare databases have been increasingly used for epidemiological purposes [7]. In addition to demographics and LTD status for MS, further data are now available in these databases, namely, reimbursements for disease-modifying treatments, disability pensions for MS, and hospitalisation for MS.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The existing body of research on PD epidemiology suggests that disease frequency peaks in the age-group 80-89 years old and then declines; 5,16,17 other studies have found the highest agespecific prevalence rates among the oldest groups studied. [13][14][15] The existing body of research on PD epidemiology suggests that disease frequency peaks in the age-group 80-89 years old and then declines; 5,16,17 other studies have found the highest agespecific prevalence rates among the oldest groups studied.…”
mentioning
confidence: 98%
“…[13][14][15] The existing body of research on PD epidemiology suggests that disease frequency peaks in the age-group 80-89 years old and then declines; 5,16,17 other studies have found the highest agespecific prevalence rates among the oldest groups studied. 3,7,11,14,15,[17][18][19] Several other studies did not observe a statistically significant difference between gender and adjusted PD prevalence rates. Males have been related to higher age-adjusted prevalence rates in many studies; in only a few studies did females have higher rates.…”
mentioning
confidence: 98%